2018
DOI: 10.1182/bloodadvances.2018023267
|View full text |Cite
|
Sign up to set email alerts
|

Intima-media thickness of the common femoral artery as a marker of leg ulceration in sickle cell disease patients

Abstract: Leg ulceration is a debilitating chronic complication of sickle cell disease (SCD) the pathogenesis of which is yet to be fully elucidated. We hypothesized that SCD patients with histories of previous leg ulcers would have intima hyperplasia of the common femoral artery (CFA). We enrolled 44 SCD patients and 33 age-matched and sex-matched controls with hemoglobin AA. Anthropometric measurements, biochemical parameters, and sonographic intima-media thickness (IMT) of the CFA were determined. The median CFA IMT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…35 In Nigerians with hypertension, carotid and femoral thickness increased significantly compared to healthy subjects and the thick femoral IMT was one of the pinpoints of atherosclerosis. 36 Our results showed that the percentage of femoral atherosclerosis was significantly higher in patients with high 24-h MAUS and low eGFR when compared with those with normal eGFR and negative 24-h MAUS. Theoretically, microalbuminuria and chronic kidney diseases are the risks of cardiovascular disease and contributed to the abnormal changes of endothelial function.…”
Section: The Prevalence Of Abnormal Femoral Arterial Intima-media Thimentioning
confidence: 44%
“…35 In Nigerians with hypertension, carotid and femoral thickness increased significantly compared to healthy subjects and the thick femoral IMT was one of the pinpoints of atherosclerosis. 36 Our results showed that the percentage of femoral atherosclerosis was significantly higher in patients with high 24-h MAUS and low eGFR when compared with those with normal eGFR and negative 24-h MAUS. Theoretically, microalbuminuria and chronic kidney diseases are the risks of cardiovascular disease and contributed to the abnormal changes of endothelial function.…”
Section: The Prevalence Of Abnormal Femoral Arterial Intima-media Thimentioning
confidence: 44%
“…SCD is associated with a progressive vasculopathy that has been demonstrated in several vascular territories, including the cerebral circulation where it is implicated in predisposition to stroke . It has also been implicated in the development of pulmonary hypertension, leg ulceration, and priapism . The blood velocity changes of the celiac and SMAs seen in this case series on Doppler ultrasonography are probably a result of this vasculopathy.…”
Section: Discussionmentioning
confidence: 62%
“…8 It has also been implicated in the development of pulmonary hypertension, leg ulceration, and priapism. 9,25 The blood velocity changes of the celiac and SMAs seen in this case series on Doppler ultrasonography are probably a result of this vasculopathy.…”
Section: Case Seriesmentioning
confidence: 76%
“…ED has been implicated in the chronic arterial vasculopathy seen in patients with SCD, which is said to be responsible for diverse multiorgan pathologies (18). Ultrasonography has proven to be useful in assessing vasculopathic changes of the cerebral arteries (19,20), renal arteries (21,22), and femoral arteries (23) in SCD. In contrast to these arteries, which reflect changes to localized regions of the body, FMD of the brachial artery has the advantage of giving an overview of the overall vascular health of the body.…”
Section: Discussionmentioning
confidence: 99%
“…Sherwood et al (46) confirmed that patients with SCD had reduced erythropoietin levels in comparison with a control population. Tissue ischemia and infarction resulting from vascular occlusion in SCD are primarily due to the microvascular obstruction by SRBC, although vasculopathic changes in larger vessels are also known to affect the kidneys ( Figure 2) (23,47,48). Circulating microparticles found in patients with end stage renal failure have been associated with ED, which is a significant determinant of cardiovascular risk (49).…”
Section: Discussionmentioning
confidence: 99%